Friction Influence on the Accuracy of the Rotors Automatic Balance - Ziyakaev G. R. Gregory Rakitovich; Gorbenko M. V. Mikhail Vladimirovich; Gorbenko T. I. Tatiana Ivanovna; Ivkina O. P. (Mechanical Engineering Technology, 2016)
Title screen